2020
DOI: 10.1109/jstars.2020.3022210
|View full text |Cite
|
Sign up to set email alerts
|

Improved Mapping Results of 10 m Resolution Land Cover Classification in Guangdong, China Using Multisource Remote Sensing Data With Google Earth Engine

Abstract: Land cover information depicting the complex interactions between human activities and surface change is critically essential for nature conservation, social management, and sustainable development. Recent advances have shown great potentials of remote sensing data in generating high-resolution land cover maps, but it remains unclear how different models, data sources, and inclusive features affect the classification results, which hinders its applications in regional studies requiring more accurate land cover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 62 publications
(74 reference statements)
0
5
0
Order By: Relevance
“…Given the true land class was unknown, we selected 30 m CLUDs as target data, used 500 m MCD12Q1 as ancillary data to carry out the spatial stratification, and employed 10-m FROM-GLC10, which had a higher spatial resolution and more reliable global/regional accuracy [31,32], as reference data to measure the sampling efficiency in the case study. However, in application of the proposed spatial stratification method, products with different resolutions should be used in the stratification as much as possible, and reference data, e.g., FROM-GLC10, can be also used for spatial stratification.…”
Section: Discussionmentioning
confidence: 99%
“…Given the true land class was unknown, we selected 30 m CLUDs as target data, used 500 m MCD12Q1 as ancillary data to carry out the spatial stratification, and employed 10-m FROM-GLC10, which had a higher spatial resolution and more reliable global/regional accuracy [31,32], as reference data to measure the sampling efficiency in the case study. However, in application of the proposed spatial stratification method, products with different resolutions should be used in the stratification as much as possible, and reference data, e.g., FROM-GLC10, can be also used for spatial stratification.…”
Section: Discussionmentioning
confidence: 99%
“…Among the various supervised and unsupervised classification methods, Machine Learning (ML) methods have become a prominent focus of RS for wetland mapping [22]. It has been widely reported that among different ML classification techniques, RF achieves better performance for wetland mapping [8,[23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…GEE is a cloud-based computing platform that includes massive amounts of open access earth observation datasets, image processing, and classification algorithms [25,30]. The availability of many datasets and ready-to-use image-driven products, easy downloading and uploading of data in various formats, and access to many image processing and ML algorithms are some of the features that have contributed to the widespread use of GEE [30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…The fusion of optical and SAR data is an active area of research and it has proven successful for different remote sensing tasks [7,8]. In this regard, S1 and S2 complement each other perfectly due to their different characteristics, facilitating the mapping tasks [9], although few works have considered using them together for pixel-wise labeling purposes [10,11]. In fact, to the best of our knowledge, there is no prior work combining S1 and S2 for building and road detection.…”
Section: Introductionmentioning
confidence: 99%